Case Report: Sparganosis in Domestic Cat - Samosir, Hartina; Putriningsih, Putu Ayu Sisyawati; Suartha, I Nyoman (Indonesia Medicus Veterinus, 2019)
Sparganosis is one of the food borne zoonotic diseases caused by the plerocercoid larvae (spargana) of the Spirometric genus. Sparganosis cases in five-month-old female cats in Denpasar, Bali were reported by us. Clinical sign of a Spirometric tapeworm infection in the case cat of the fecal consistency is grade 3.5. These findings are reported from animal’s owners who found worms when defecate. Eggs per gram (EPG) 16,900 it shows the intensity of spirometra infection in cat high enough. The Animal were treated with praziquantel 0.5 tablets, given twice with a seven-day interval. Evaluation of the cat after two times treatments for clinical signs of significant changes only from the fecal effusion from grade 3.5 to grade 2 was well formed, does not leave a mark when picked up.